Study on adaptive heat transfer performance of high temperature heat pipe. (1st December 2021) - Ji, Yang; Yuan, Dazhong; Che, Zhanxun; Zhao, Jie; Tang, Dawei; Zhang, Zhuohua
Highlights: In this paper, several high temperature heat pipes with good heat transfer performance are designed and prepared. The test-bed for frozen startup and heat transfer performance of HTHP is set up. The experimental study on the adaptive heat transfer characteristics of HTHP are systematically carried out. The key influencing factors of adaptive heat transfer characteristics are summarized. Abstract: High temperature heat pipe (HTHP) employs alkali metal or its alloy as working fluid. Due to the large latent heat of its working fluid during phase change heat transfer, HTHP has the advantages of high temperature uniformity, high working temperature and high intensity heat transfer capacity, which has broad application prospects in the field of HTHP cooled nuclear reactors and the thermal protection of hypersonic vehicles. In order to simplify the structure of heat transfer system in nuclear reactors, so that it can safely and reliably realize passive heat transfer without additional pump power under various operating conditions, HTHP must have adaptive heat transfer capacity. In this paper, several HTHPs with excellent heat transfer performance are designed and prepared. The test-bed for frozen startup and heat transfer performance of HTHP is set up, and the electromagnetic induction high frequency heater is used as high temperature heat source. The thermal performance of HTHP with different heating power, heating position and the length of evaporation section (adaptive heat transfer characteristics) is experimentally studied, and the theoretical model is used to validate the experimental result. The experimental and theoretical results show that high vacuum degree is the prerequisite for excellent heat transfer performance of HTHP; high capillary driving force and suction force, reasonable filling ratio of working fluid are the key factors for HTHP to have adaptive heat transfer capacity, and the diameter of HTHP also has important influence on adaptive heat transfer capacity.